Seroprevalence of hepatitis B surface antigen and antibody to hepatitis C virus at a tertiary care centre in Telangana - Tripathi, Purti Chandrashekher; Chakraverti, Trinain Kumar; Khant, Nileshkumar Ramniklal (International Journal of Research in Medical Sciences, 2017)
Background:Hepatitis B Virus (HBV) and Hepatitis C Virus (HCV) are serious public health problem worldwide and major causes of chronic hepatitis, liver cirrhosis and hepatocellular carcinoma. The purpose of this study was to estimate the prevalence rates of HBV and HCV infections in this part of country. Methods:Serum samples of inpatients and outpatients were collected over a period of one and a half year. HBsAg was determined using the HBsAg one step (HEPACARD) hepatitis B surface antigen test device. Antibody detection of HCV was done using HCV TRI-DOT. Results:A total of 4369 serum samples were tested for HBsAg detection and 736 serum samples were tested for hepatitis C virus antibodies. Seropositivity for HBsAg was 1.69% whereas HCV seropositivity was 0.4%. A higher seroprevalence of HBsAg and HCV was found in males as compared with females. Conclusion:Attempts should be made to reduce the incidence of HCV and HBV and their unregulated spread which can be done by increasing public awareness of simple preventive measures.